182k views
4 votes
X + 5y +3z = 4
4y – z=3
6x – 2y + 4z = 0

1 Answer

4 votes

Answer:

x =
(1)/(4)

y =
(3)/(4)

z = 0

Explanation:

You first need to solve for a variable, it won't be as easy as x = 3, you are looking to replace a variable with another equation.

For example, the second equation, 4y-z=3, I can either solve for y or z. It won't be a numerical value but it will get you a step closer.

4y-z=3

4y=z+3

y =
(z)/(4) +(3)/(4)

Then you are able to use substitution to negate one of the variables and solve for the other two variables. I won't type that but I think you get the idea.

User Ganesh Satpute
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.